Enhancing Cardiovascular Dynamics by Inhibition of Thrombospondin-1/CD47 Signaling - Isenberg, Jeff S. (2008)
Activation of soluble guanylate cyclase by nitric oxide (NO) controls signaling pathways that play critical roles in normal vascular physiology and in the pathogenesis of cardiovascular disease. We have identified the secreted protein thrombospondin-1 as a key regulator of NO signaling. Thrombospondin-1 limits the angiogenic activity of NO in endothelial cells, its vasodilator activity in vascular smooth muscle, and its antithrombotic activity in platelets. Loss of either thrombospondin-1 or its receptor CD47 in transgenic mice results in hyperdynamic responses to NO and reveals the importance of this pathway in normal physiology. Thrombospondin-1 and CD47 null mice show improved abilities to respond to ischemic stress, suggesting that therapeutic targeting of this pathway could benefit patients with a variety of ischemic conditions. We review the preclinical development of therapeutics targeting thrombospondin-1 or CD47 for improving survival of fixed ischemia, ischemia due to aging and peripheral vascular disease, and skin grafting.